2013
DOI: 10.1007/s11605-012-2045-9
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Obesity and Colorectal Cancer: Are We Missing the Boat with BMI?

Abstract: This study shows that viscerally obese patients with stage II colorectal cancer are at higher risk for poor outcomes and should be increasingly considered for adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 35 publications
7
123
1
4
Order By: Relevance
“…Furthermore, regardless of BMI, women appear to have higher levels of SFA and fat mass than men. 8,10,16,17,28 Similarly, in the current study the correlation between BMI and VFA (r = 0.542) was relatively weak when compared to that of BMI and SFA (r = 0.804) and BMI and TFA (r = 0.846). In addition, women had higher SFA but lower VFA than men, but did not differ from men with regard to BMI or TFA.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Furthermore, regardless of BMI, women appear to have higher levels of SFA and fat mass than men. 8,10,16,17,28 Similarly, in the current study the correlation between BMI and VFA (r = 0.542) was relatively weak when compared to that of BMI and SFA (r = 0.804) and BMI and TFA (r = 0.846). In addition, women had higher SFA but lower VFA than men, but did not differ from men with regard to BMI or TFA.…”
Section: Discussionsupporting
confidence: 50%
“…6 Visceral fat has been identified as an independent risk factor and a predictor of outcome in several cancers, including breast, esophageal, colorectal and pancreatic cancers. [7][8][9][10][11] Altered metabolism has a central role in RCC pathogenesis, possibly explaining the link between obesity and RCC. 4,12 While the reported effects of BMI on RCC have been uniform, reports concerning the effect of visceral adiposity on the pathological and clinical outcomes of RCC are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BMI, frequently associated with dyslipidemia [1], was not sensitive for differences in lipid plasmatic profile. Apart from the fact that BMI-defined obesity has missed the detection of subclinical inflammation in our study, it has also been reported that visceral fat measurements elucidate relationships between obesity and cancer otherwise not significant when evaluated by BMI [43]. …”
Section: Discussionmentioning
confidence: 70%
“…Ряд авторов указывают, что не выявили различий во времени проведения операции, качестве препарата ТМЭ, развитии интраоперационных осложнений, количестве удаленных лимфати-ческих узлов у пациентов с нормальным и по-вышенным ИМТ [13,14]; более того, отмечено что всем пациентам, которым планируется вы-полнение операции по поводу рака средне-и нижнеампулярного отдела прямой кишки, в обязательном порядке необходимо определять индекс висцерального ожирения как наибо-лее чувствительного фактора, оценивающего влияние висцерального жира на выполнение операций по поводу рака прямой кишки [14].…”
Section: Discussionunclassified